Physical and chemical properties of recombinant human tissue kallikrein and porcine pancreatic kallikrein - GAO Bo; SUN Huai-chang; SONG Cheng-yi (浙江大学学报. 农业与生命科学版)
To study the similarity between recombinant human tissue kallikrein (rhK1) and natural kallikrein, the physical and chemical properties of rhK1 expressed in chicken oviduct transient bioreactor and porcine pancreatic kallikrein (pK) were compared. Western blotting analysis showed the rhK1 was recognized specifically by hKl antibody, and two bands with molecular weights of 37 kDa and 43 kDa were observed, corresponding to the mature- and pre-enzyme respectively, but pK failed to react with the antibody. Biochemical studies showed that the rhK1 was stable from pH 7 to pH 10, while pK was stable from pH 8 to pH 9, the activity of rhKl and pK was inhibited completely by Cu2+, Fe3+ and Al3+. The rhKl and pK showed similar thermo-stability, but rhKl was activated significantly after 20 minutes with 37℃ incubation. These data indicated that the molecular weight of rhKl was right, rhK1 and pK had similar thermo-stability, optimal pH value and sensitivity to ions, and the chicken oviduct-specific transient expression system can be used to produce commercial recombinant proteins.